Integration Of Remote Sensing And Magnetic Methods For Geological Mapping Of Central Zagros Area - Mohajerin, Ashkan (2011)
In this project, Thematic Mapper (TM), Digital Elevation Model (DEM) images and PALSAR Radar images were used to study the geological features of Gardaneh Rokh and Jahan Bin area in Iran. Magnetic Grand Survey data and Aero Magnetic data from these two areas were also used for the purpose of the study. The scanned geological maps and Aero Magnetic maps which were geometrically corrected were used with TM, PALSAR and DEM images to extract geological information. The geological map was used as reference or ground truth data. Several analyses have been done to the images such as colour composite, principal component analysis, ratio, supervised classification, and lineament. In order to evaluate the classification process, accuracy assessment was done to the classified images.